Investigating body patterning in aquarium-raised flamboyant cuttlefish (Metasepia pfefferi) - Amber Thomas; Christy MacDonald (PeerJ, 2016)
Cuttlefish are known for their ability to quickly alter their total appearance, or body pattern, to camouflage or to communicate with predators, prey and conspecifics. The body patterns of some species have been extensively documented to gain a better understanding of their behaviors. However, the flamboyant cuttlefish (Metasepia pfefferi) is largely unstudied. Recently, aquarists have been able to breed, house and display M. pfefferi, giving researchers ample opportunities to study their behavior under those conditions. This study aimed to identify the dorsally-visible components of the body patterns used by 5 sexually-mature, freely-behaving, F5 generation M. pfefferi in their home aquarium at The Seas in Epcot at Walt Disney World Resorts®, Lake Buena Vista, FL, USA. Furthermore, we aimed to determine the most probable patterns used by this population of animals and to create a database of components that can be used in future behavioral studies. We found that this population of M. pfefferi use a combination of 7 textural, 14 postural, 7 locomotor and between 42 and 75 chromatic components in their home aquarium. Using maximum likelihood analysis and AutoClass@IJM software, we found that these components combine to generate 11 distinct body patterns. The software was able to sort 98% of the live animal observations into one of the 11 patterns with 90% confidence and 88% of observations with 99% confidence. Unusually for cuttlefish, 8 of the 11 identified patterns contained at least one “traveling” component (i.e., traveling waves or blinking spots) in which the colors on the skin appeared to travel on the animal’s mantle. In other species, these components are generally seen during hunting or aggression, but this population of M. pfefferi uses them frequently during a variety of contexts in their home aquarium. With few published data on the behavior of M. pfefferi in their natural environment, we cannot compare the behavior of the tank-raised individuals in this study to animals in the wild. However, this study provides the groundwork necessary for future studies of M. pfefferi body patterning and behavior.